2014
DOI: 10.1371/journal.pgen.1004098
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Link between Sex and Nutrition; doublesex Regulates Sex-Specific Mandible Growth via Juvenile Hormone Signaling in Stag Beetles

Abstract: Sexual dimorphisms in trait expression are widespread among animals and are especially pronounced in ornaments and weapons of sexual selection, which can attain exaggerated sizes. Expression of exaggerated traits is usually male-specific and nutrition sensitive. Consequently, the developmental mechanisms generating sexually dimorphic growth and nutrition-dependent phenotypic plasticity are each likely to regulate the expression of extreme structures. Yet we know little about how either of these mechanisms work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
150
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(155 citation statements)
references
References 45 publications
(80 reference statements)
4
150
0
1
Order By: Relevance
“…It is worth noting that both larval growth conditions and feeding resources (Moczek 2002) have an effect on the developmental mechanisms that regulate the elaboration of exaggerated structures in holometabolous insects (Shingleton et al 2008). Indeed, it has been demonstrated that in stag beetles, the development of SSC is closely associated with larval feeding conditions, the mediatory function of the juvenile hormone (Gotoh et al 2011) and the expression of transcription factors encoded by double-sex genes (Gotoh et al 2014). Larvae of the studied populations, described above, have grown in different woodland types (e.g., oak grove, chestnut) and have experienced different nutritional conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that both larval growth conditions and feeding resources (Moczek 2002) have an effect on the developmental mechanisms that regulate the elaboration of exaggerated structures in holometabolous insects (Shingleton et al 2008). Indeed, it has been demonstrated that in stag beetles, the development of SSC is closely associated with larval feeding conditions, the mediatory function of the juvenile hormone (Gotoh et al 2011) and the expression of transcription factors encoded by double-sex genes (Gotoh et al 2014). Larvae of the studied populations, described above, have grown in different woodland types (e.g., oak grove, chestnut) and have experienced different nutritional conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has implicated the sex determination gene dsx in promoting horn formation in males subject to optimal nutritional condition in both the rhinoceros beetle Trypoxylus dichotomus (which exhibits a linear, highly positive allometry) and O. taurus (which exhibits a more derived sigmoidal allometry, including a sharp body size threshold separating alternative male morphs). In both taxa, dsx seems to play a critical role in the nutrition-dependent exaggeration of horn growth, and several studies suggest further that insulin signaling, juvenile hormone signaling, or a combination of the two may interact with dsx and sensitize dsx action to nutritional conditions (24,25,27). This research highlights a third highly conserved but previously overlooked pathway, the Hh signaling pathway, whichlike dsx signaling-has been co-opted into the regulation of horn development and acquired nutrition sensitivity in the process but exerts its regulatory function in, to the best of our knowledge, a thus far unprecedented manner, namely by actively inhibiting horn growth in low-nutrition individuals only (Fig.…”
Section: Functional Significance Of Hh Signaling In the Development Omentioning
confidence: 99%
“…Previous studies have shown that horn development is instructed by many of the same genes that regulate the formation of regular appendages, such as leg gap genes (14), that nutrition responsiveness of horn development may be coupled to insulin signaling (24,25), and that sex-and morph-specific horn exaggeration may be facilitated by doublesex (dsx), a master regulator of somatic sex determination (23,26,27). However, how beetle horns achieve their strikingly dimorphic expression in many species and the developmental mechanisms that enable the definition of a sharp body size threshold separating alternate morphs from what is presumed to be a continuous range of nutritional conditions are entirely unknown.…”
mentioning
confidence: 99%
“…In striking contrast, downregulation of dsxf in female O. taurus induces nutrition-responsive development of male-like head horns (Kijimoto et al, 2012) in typically hornless females. Thus, dsx plays a critical role in the regulation of both sexual dimorphism and male polyphenism in O. taurus , and independent studies in rhinoceros beetles (Ito et al, 2013) and stag beetles (Gotoh et al, 2014) have since confirmed that sex-specific dsx isoforms have repeatedly evolved to not just inhibit the formation of weapons in females, but also to disproportionately enhance their growth in high-nutrition males.…”
mentioning
confidence: 98%